Implementation of child friendly regency program in Central Lampung: civil rights and freedoms cluster - Hutagalung, Simon Sumanjoyo; Hermawan, Dedy; Suryanta, I Wayan Ari (Publisia: Jurnal Ilmu Administrasi Publik, 2024)
Central Lampung Regencyâ€™s intermediate status as a Child-Friendly Regency underscores the need for a deeper examination of its implementation, particularly in the crucial civil rights and freedoms cluster. Despite the award, achieving the Main category requires a comprehensive understanding of existing challenges and opportunities. This research aims to (a) assess the current performance of Central Lampung Regency in the KLA Cluster I, (b) identify critical obstacles hindering progress in this cluster, and (c) formulate actionable recommendations to elevate the regency’s KLA status. This study used a qualitative approach with a descriptive method that used document data sources and FGDs. At the same time, data analysis was carried out using the Miles & Huberman Model. The results identified that the three indicators in this cluster have not reached the maximum and still face various structural and technical obstacles in achieving the cluster